Perspective pharmaceutique de la recherche clinique sur les médicaments au Québec et en France - Guérin, Aurélie; Tanguay, Cynthia; Lebel, Denis; Bourdon, Olivier; Bussières, Jean-François (Pharmactuel, 2015)
-